Editorial - Sumner-Smith, G. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Emeritus Professor Wade O. Brinker, DVM, MS, Diplomate - American College of Veterinary Surgeons whose eightieth birthday took place on the 10th of October, 1992.